Langgar dan Peran Kiai Langgar dalam Peningkatan Pendidikan Agama Islam Desa Kertanegara - Iqri Masfuroh; Ageng Widodo (IAIN Sorong, 2021)
Education in now faced with demand in preparing the complex dynamics that incapable of this rapid change that develops.Important for family and environment in providing education for children.One education have develops in family environment is.Education center have as villages have substantial and functional relation, the education to the activity not serves as an instrument as planting is he the doctrines.In a is one kiai, have where kiai usually the priest langar.In writing is better understand kiai have in the role in education islam in village kertanegara.Methods used was to utilize the qualitative method that produces descriptive in data is depiction in data analysis and data. Data collection method used is observation. Observation is conducted by seeing field condition. After data observation writer gather and based on order planned meeting.Next writer do sparingly in an effort to understand the interpretation that is to draw a conclusion.